2020
DOI: 10.3847/2041-8213/ab6f0a
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Turbulent Fast Magnetic Reconnection Observed in the Solar Atmosphere

Abstract: Fast magnetic reconnection powers explosive events throughout the universe, from gamma-ray bursts to solar flares. Despite its importance, the onset of astrophysical fast reconnection is the subject of intense debate and remains an open question in plasma physics. Here we report high-cadence observations of two reconnection-driven solar microflares obtained by the Interface Region Imaging Spectrograph that show persistent turbulent flows preceding flaring. The speeds of these flows are comparable to the local … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
3
27
0
Order By: Relevance
“…A more recent study exploring the growth of the thickness of the reconnection layer of the microflaring loop is presented in Chitta and Lazarian (2019). This study shows that the turbulent velocity measured using Doppler-broadened lines and the width of the reconnection region are in a good agreement with the predictions of the LV99 theory.…”
Section: A Solar Flaressupporting
confidence: 53%
“…A more recent study exploring the growth of the thickness of the reconnection layer of the microflaring loop is presented in Chitta and Lazarian (2019). This study shows that the turbulent velocity measured using Doppler-broadened lines and the width of the reconnection region are in a good agreement with the predictions of the LV99 theory.…”
Section: A Solar Flaressupporting
confidence: 53%
“…Similarly, we have also not explored the physics of reconnection onset itself which is likely governed by highly dynamic current sheets and plasma evolution (e.g. Priest & Heyvaerts 1974;Heyvaerts et al 1977;Chitta & Lazarian 2020). Nevertheless, as a first step, our observations emphasise the additional role of footpoint reconnection driven by interacting mixed magnetic polarities in impulsive atmospheric heating, including coronal heating to several million degrees Kelvin.…”
Section: Discussionmentioning
confidence: 91%
“…For example, strong emission in the wings of Hα would imply reconnection in the lower atmosphere, whereas bright Mg ii h and k, Si iv 1393.7, 1402.8 Å or even extreme-ultraviolet (EUV) emission would originate in higher layers. Other key signatures such as recurrence, intermittency, and large flow velocities may be caused by the release of fast-moving sequences of magnetic islands (or plasmoids) and jets (e.g., Karpen et al 1995;Shibata & Tanuma 2001;Bhattacharjee et al 2009;Innes et al 2015;Ni et al 2015;Rouppe van der Voort et al 2017;Peter et al 2019), while turbulence has also been shown to potentially play a role in triggering fast reconnection in MFs (e.g., Chitta & Lazarian 2020).…”
Section: Introductionmentioning
confidence: 99%